IMPLEMENTASI IJTIHAD YUSUF QARDHOWI TENTANG ZAKAT - Ahmad Sibawai; Rus Yandi (LPPM Universitas Ekasakti, 2024)
Islam is a teaching that requires attention to those who are in poverty. Islam's desire to help and lift them from the brink of poverty is applied by paying zakat in the Islamic religion. Zakat, which has been interpreted traditionally, has been disrupted by Yusuf Qardhawi by creating many new categories regarding zakat. Among the new categories of the results of Yusuf Qardhawi's Ijtihad in the book of Fiqh Zakat are, Zakat on Honey and Animal Production, zakat on investment in factories, buildings and others, zakat on pursuits and professions as well as zakat on shares and bonds as well as zakat on marine products which includes amber pearls and others. other. The rule used by Yusuf Qardhawi in expanding the category of obligatory zakat assets is, relying on general propositions, in addition to adhering to the requirements for obligatory zakat assets, namely growth and development. Either grow and develop through effort or based on the substance of the treasure that develops.